3-D-display - Omeltshenko, Svitlana (Видавництво Львівської політехніки, 2010)
In this paper are given a brief description of the work and the basic advantages and disadvantages of 3- D-displays.
Keywords: 3-D-display; the anaglyph stereo; principle of spectral separation; principle of temporary separation; principle of spatial separation